Innovation and Economic Development - Hatakenaka, Sachi (International Higher Education, 2010)
Universities are going through significant organizational changes to play appropriate roles in innovation and economic development. Many universities are setting up appropriate institutional policies, processes, and incentives, and having technology-transfer offices for research-related functions. Changing people's attitudes as well as interaction with science parks are other issues. Many universities are undertaking interdisciplinary research. Large-scale partnerships with industry are increasingly established through institutional leaderships.